Description of Hypertension Management in The Elderly at PSTW Khusnul Khotimah Riau Province - Amelia, Heni; Hasneli N, Yesi; Huda, Nurul (CV. Rayyan Dwi Bharata, 2025)
Management of hypertension in the elderly often faces challenges, such as difficulties in monitoring blood pressure, compliance with treatment, and the presence of comorbidities. This study aims to determine the description of hypertension management in the elderly. This research is a quantitative research with a descriptive approach on 38 elderly people at PSTW Khusnul Khotimah Social Service of Riau Province with the criteria being elderly people aged 60-90 years. Respondents were in the elderly age category (60-74 years), namely 73.7% and 57.9% female, and the highest level of education was elementary school 28.9%. It was found that 68.4% of respondents did not have comorbidities and 73.7% of respondents did not have a family history of hypertension. The results of the research show that the picture of hypertension management in the elderly at UPT PSTW Khusnul Khotimah Social Service of Riau Province is that 52.6% of respondents have poor hypertension management, while 47.4% of respondents have good management.